2015
DOI: 10.5301/ejo.5000671
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Artery Blood Flow Parameters in Pseudoexfoliation Glaucoma

Abstract: The results support the findings of increased vascular resistance in OA XFG. High sensitivity and specificity obtained for OA RI may be useful in evaluation of future therapeutic vascular agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…25 Impaired retrobulbar hemodynamics have been identified in exfoliation syndrome and exfoliation glaucoma. [26][27][28] However, these methods have not been established in everyday clinical practice for various reasons, e.g., due to invasiveness (fluorescein angiography) or, especially, because an individual diagnosis is not possible on the basis of circulatory abnormalities alone or because of a lack of quantifiable parameters. Owing to these difficulties, the diagnosis of perfusion disorders is often based on the presence of indirect signs such as vasospastic syndrome, arterial hypotension, migraine, or tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…25 Impaired retrobulbar hemodynamics have been identified in exfoliation syndrome and exfoliation glaucoma. [26][27][28] However, these methods have not been established in everyday clinical practice for various reasons, e.g., due to invasiveness (fluorescein angiography) or, especially, because an individual diagnosis is not possible on the basis of circulatory abnormalities alone or because of a lack of quantifiable parameters. Owing to these difficulties, the diagnosis of perfusion disorders is often based on the presence of indirect signs such as vasospastic syndrome, arterial hypotension, migraine, or tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not only demonstrated that PEX material is correlated with vascular dysfunction, but have also identified it as an independent risk factor (6). In a recent study comparing ophthalmic arterial hemodynamics and vascular resistance in eyes with PEX and healthy eyes, Kocaturk et al (12) reported an increase in vascular resistance and disruption of hemodynamic parameters in PEX eyes. The results of our study corroborate previous studies demonstrating retinal blood flow abnormalities in patients with PEX compared with healthy individuals (6,10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The mean velocity and the resistivity index (RI) are the two important parameters that can be followed, except that RI does not accurately correlate with the resistance offered by the ophthalmic vessels [ 17 , 18 ]. Kocaturk et al reported increased vascular resistance in OA in pseudoexfoliation glaucoma [ 19 ]. Many studies demonstrated that the blood flow resistance was increased and blood flow velocities were decreased in the OA and SPCAs of patients with POAG, pseudoexfoliation syndrome, and NTG [ 9 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kocaturk et al reported increased vascular resistance in OA in pseudoexfoliation glaucoma [ 19 ]. Many studies demonstrated that the blood flow resistance was increased and blood flow velocities were decreased in the OA and SPCAs of patients with POAG, pseudoexfoliation syndrome, and NTG [ 9 , 17 19 ]. Reduced blood flow velocities and increased RI in retrobulbar vessels in patients with NTG may explain the reason for the ONH fluorescein filling defects and capillary loss of the ONH of these patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%